Finite packing and covering - Böröczky, K. (Cambridge tracts in mathematics ;, 2004)
Annotation This book provides an in-depth, state-of-the-art discussion of the theory of finite packings and coverings by convex bodies. It contains various new results and arguments, collects other key data scattered about the literature, and provides a comprehensive treatment of problems whose interplay was not clearly understood prior to this text. Arrangements of congruent convex bodies in Euclidean space are covered, and the density of finite packing and covering by balls in Euclidean, spherical and hyperbolic spaces is considered.